'Pain‐free TRUS B': a phase 3 double‐blind placebo‐controlled randomized trial of methoxyflurane with periprostatic local anaesthesia to reduce the discomfort of transrectal ultrasonography‐guided prostate biopsy (ANZUP 1501). (30th July 2021) - Hayne, Dickon; Grummet, Jeremy; Espinoza, David; McCombie, Steve P.; Chalasani, Venu; Ford, Kate S.; Frydenberg, Mark; Gilling, Peter; Gordon, Barbara; Hawks, Cynthia; Konstantatos, Alex; Martin, Andrew J.; et al.
Abstract : Objective: To determine whether the addition of inhaled methoxyflurane to periprostatic infiltration of local anaesthetic (PILA) during transrectal ultrasonography‐guided prostate biopsies (TRUSBs) improved pain and other aspects of the experience. Patients and Methods: We conducted a multicentre, placebo‐controlled, double‐blind, randomized phase 3 trial, involving 420 men undergoing their first TRUSB. The intervention was PILA plus a patient‐controlled device containing either 3 mL methoxyflurane, or 3 mL 0.9% saline plus one drop of methoxyflurane to preserve blinding. The primary outcome was the pain score (0–10) reported by the participant after 15 min. Secondary outcomes included ratings of other aspects of the biopsy experience, willingness to undergo future biopsies, urologists' ratings, biopsy completion, and adverse events. Results: The mean (SE) pain scores 15 min after TRUSB were 2.51 (0.22) in those assigned methoxyflurane vs 2.82 (0.22) for placebo (difference 0.31, 95% confidence interval [CI] −0.75 to 0.14; P = 0.18). Methoxyflurane was associated with better scores for discomfort (difference −0.48, 95% CI −0.92 to −0.03; P = 0.035, adjusted [adj.] P = 0.076), whole experience (difference −0.50, 95% CI −0.92 to −0.08; P = 0.021, adj. P = 0.053), and willingness to undergo repeat biopsies (odds ratio 1.67, 95% CI 1.12–2.49; P = 0.01) than placebo. Methoxyflurane resulted in higher scores for drowsiness (difference +1.64, 95% CI 1.21–2.07; P < 0.001, adj. P < 0.001) and dizziness (difference +1.78, 95% CI 1.31–2.24; P < 0.001, adj. P < 0.001) than placebo. There was no significant difference in the number of ≥ grade 3 adverse events. Conclusions: We found no evidence that methoxyflurane improved pain scores at 15 min, however, improvements were seen in patient‐reported discomfort, overall experience, and willingness to undergo repeat biopsies.